Redox-Regulation of Photorespiration through Mitochondrial Thioredoxin o1. Issue 2 (14th August 2019) - Reinholdt, Ole; Schwab, Saskia; Zhang, Youjun; Reichheld, Jean-Philippe; Fernie, Alisdair R.; Hagemann, Martin; Timm, Stefan
Abstract : The mitochondrial thioredoxin o1 contributes to the redox-regulation of photorespiration via regulation of the activation state of mitochondrial lipoamide dehydrogenase. Abstract: Photorespiration sustains photosynthesis in the presence of oxygen due to rapid metabolization of 2-phosphoglycolate, the major side-product of the oxygenase activity of Rubisco that also directly impedes carbon assimilation and allocation. Despite the fact that both the biochemical reactions and the underlying genetics are well characterized, information concerning the regulatory mechanisms that adjust photorespiratory flux is rare. Here, we studied the impact of mitochondrial-localized thioredoxin o1 (TRXo1) on photorespiratory metabolism. The characterization of an Arabidopsis ( Arabidopsis thaliana ) transfer DNA insertional line ( trxo1-1 ) revealed an increase in the stoichiometry of photorespiratory CO2 release and impaired Gly-to-Ser turnover after a shift from high-to-low CO2 without changes in Gly decarboxylase (GDC) gene or protein expression. These effects were distinctly pronounced in a double mutant, where the TRXo1 mutation was combined with strongly reduced GDC T-protein expression. The double mutant ( TxGT ) showed reduced growth in air but not in high CO2, decreased photosynthesis, and up to 54-fold more Gly alongside several redox-stress-related metabolites. Given that GDC proteins are potential targets for redox-regulation, we also examined the in vitro properties of recombinant GDC l -proteins (lipoamide dehydrogenase) from plants and the cyanobacterium Synechocystis species strain PCC6803 and observed a redox-dependent inhibition by either artificial reducing agents or TRXo1 itself. Collectively, our results demonstrate that TRXo1 potentially adjusts photorespiration via redox-regulation of GDC in response to environmental changes.